Elementy językowego obrazu świata w nauczaniu języka francuskiego w kontekście filologicznym - Dryjańska, Agnieszka (Neofilolog, 2024)
In teaching French as a foreign language in the philological context, insufficient attention is paid to the development of lexical and semantic competences, especially in relation to culture. The linguistic worldview is an ethnolinguistic concept that integrates many different lexical phenomena such as polysemy, derivation, connotation and word structures in order to show the close relationship between lexis and culture. Showing a word in a complex network of lexical-semantic-compositional relations is a tool with strong didactic potential. The aim of this study is to identify this potential in the context of teaching French vocabulary. We focus on the theoretical background of lexical and semantic competences and on the analysis of the relationship between language, culture and meaning in ethnolinguistic and cognitive terms. The empirical part explores, in a quantitative and qualitative way, the methodology of teaching lexis as it is implemented in French language textbooks. The result of our study shows that this methodology, in terms of the presentation of vocabulary and the number and types of lexical exercises, is not sufficient for learning the real meaning of words. The linguistic worldview is a tool that may meet this challenge.